Formation of supramolecular hydrogen-bonding chains and networks from copper (II) halogenobenzoates with N-methylnicotinamide: Supramolecular isomerism. (1st January 2020) - Halaška, Jozef; Lokaj, Ján; Jomová, Klaudia; Růžičková, Zdeňka; Mazúr, Milan; Moncol, Ján
Graphical abstract: The self-assembly of supramolecular structures from copper (II) halogenobenzoate complexes containing N -methylnicotinamide ligand have been explored. Crystal structures of all studied complexes have been determined using single-crystal diffraction. The compounds are monomeric complexes with a distorted octahedral or square-pyramidal coordination sphere around Cu 2+ ion. The two polymorph sets have been observed and they are examples of coordination compounds which are conformation and supramolecular isomers. The crystal structure of one complex shows the phase transition in two temperatures. The crystal structure of one compound shows coordination polymer with bridging aqua ligand. The molecules of all compounds are connected by N–H…O and O–H…O hydrogen bonds from N -methylnicotinamide and water molecules which create supramolecular hydrogen-bonding-coordination chains and networks. The intermolecular interactions were studied by Hirshfeld surface analysis. Highlights: Seventeen new copper(II) halogenobenzoate complexes with N -methylnicotinamide. The crystal structures of compounds show supramolecular H–bonding chains and networks. The crystal structures of compounds show variable structure rules of water molecules. The two sets compounds show conformation and supramolecular isomerism. The one compound shows phase-transition. Abstract: The self-assembly of supramolecular structures from copper (II) halogenobenzoate complexes containing N -methylnicotinamide ligand have been explored. The following compound and polymorph structures were determined by single-crystal X-ray structural analysis-the compounds [Cu(4-Fbz)2 (mna)2 (H2 O)], [Cu(4-Clbz)2 (mna)2 (H2 O)], [Cu(4-Brbz)2 (mna)2 (H2 O)], two polymorphs of [Cu(2, 6-Cl2 bz)2 (mna)2 (H2 O)2 ]·2H2 O, [Cu(3, 5-Cl2 bz)2 (mna)2 (H2 O)2 ]·2H2 O, [Cu(3-Fbz)2 (mna)2 (H2 O)2 ]·2H2 O, and [Cu(3-Clbz)2 (mna)2 (H2 O)2 ]·2H2 O, two polymorphs of [Cu(3-Brbz)2 (mna)2 (H2 O)2 ]·2H2 O, [Cu(3-Ibz)2 (mna)2 (H2 O)2 ]·2H2 O, [Cu(2, 5-Cl2 bz)2 (mna)2 (H2 O)2 ]·2H2 O, [Cu(2, 3-Cl2 bz)2 (mna)2 (H2 O)2 ]·H2 O, [Cu(2, 6-Cl2 bz)2 (mna)2 (H2 O)]·2H2 O, [Cu(3, 4-Cl2 bz)2 (mna)2 (H2 O)]·2H2 O, [Cu(3-Brbz)2 (mna)2 (H2 O)] and [Cu(2-Fbz)2 (mna)2 (μ-H2 O)]n, (mna =  N -methylnicotinamide, 4-Fbz = 4-fluorobenzoate, 4-Clbz = 4-chlorobenzoate, 4-Brbz = 4-bromobenzoate, 3-Fbz = 3-fluorobenzoate, 3-Clbz = 3-chlorobenzoate, 3-Brbz = 3-bromobenzoate, 3-Ibz = 3-iodobenzoate, 2-Ibz = 2-iodobenzoate, 2, 3-Cl2 bz = 2, 3-dichlorobenzoate, 2, 5-Cl2 bz = 2, 5-dichlorobenzoate, 2, 6-Cl2 bz = 2, 6-dichlorobenzoate, 3, 4-Cl2 bz = 3, 4-dichlorobenzoate and 3, 5-Cl2 bz = 3, 5-dichlorobenzoate). The compounds are monomeric complexes with a distorted octahedral or square-pyramidal coordination sphere around Cu 2+ ion. The two polymorph sets of [Cu(2, 6-Cl2 bz)2 (mna)2 (H2 O)2 ]·2H2 O and [Cu(3-Brbz)2 (mna)2 (H2 O)2 ]·2H2 O are two examples of coordination compounds which are conformation and supramolecular isomers. The crystal structure of complex [Cu(4-Fbz)2 (mna)2 (H2 O)] shows the phase transition in two temperatures. The compound [Cu(2-Fbz)2 (mna)2 (μ-H2 O)]n is a coordination polymer with bridging aqua ligand. The molecules of all compounds are connected by N–H…O and O–H…O hydrogen bonds from NHCH3 groups of N -methylnicotinamide and water molecules which create supramolecular hydrogen-bonding-coordination chains and networks. The intermolecular interactions were studied by Hirshfeld surface analysis.